ANALISIS USAHATANI PEPAYA (Studi Kasus : Kecamatan Secanggang, Kabupaten Langkat, Sumatera Utara) - Bigner Dolok Saribu; Yusniar Lubis; Mitra Musika Lubis (Universitas Medan Area, 2019)
The purpose of this study was to investigate papaya cultivation, to analyze the costs of production and acceptance and profits of papaya farmers, and to analyze the feasibility of papaya farming in Secanggang District, Langkat Regency. Research in Secanggang District, Langkat Regency, North Sumatra Province. Determination of the research area is carried out by Pusposive (intentional). The study was conducted in May - July 2017. The sampling method was conducted by census by taking 28 papaya farmers who had plant life above 1 year. The results showed the condition of land availability was 0.5 ha so that the spacing was not suitable. The cultivation technique has not been improved even though it has been experienced for 15 years. This is evidenced by the productivity of papaya land at only 19,260.51 kg / ha. While papaya land productivity is good 20-35 tons / ha. The average farmer income is Rp. 29,468,571 per farmer or Rp. 59,255,411 per hectare per year. Farming income obtained is Rp. 22,333,539 per farmer or Rp. 44,823,477 per hectare per year, and after adding the TKDK value, the family income of Rp. 23,889,254 per farmer or Rp. 48,500,888 per hectare per year. RCR value is greater than 1 so it is concluded that papaya farming in the study area is classified as feasible. Every expenditure of Rp. 1 will generate revenue of Rp. 4.13.